2023
DOI: 10.3390/app13127133
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tool Rotation Speed on the Formation of Eutectic Structure during Friction Stir Welding of Aluminum to Magnesium

Abstract: Friction stir welding (FSW) is a solid-state welding process capable of joining a wide range of light metals. However, liquation and solidification may occur during joining of dissimilar metals which leads to eutectic formation. This article aims to discover the influence of tool rotation speed on the formation of eutectic structure during friction stir welding of aluminum to magnesium. To do so, friction stir welding was performed at 600 and 950 rpm to join pure aluminum and ECO-AZ91 magnesium alloy in a lap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Guan et al [22] reported, in their review, 72-84 and 44-65 hardness (HV) for AZ91/CNT and SiC/Mg composites, respectively. Further, Dudek et al [34] found the hardness result to be 80 HBN for Mg recycled waste composites, and similar results have been reported by other researchers [35][36][37][38]. It is evident that the hardness results in the present study reflect the previously reported results.…”
Section: Hardness and Elongationsupporting
confidence: 91%
“…Guan et al [22] reported, in their review, 72-84 and 44-65 hardness (HV) for AZ91/CNT and SiC/Mg composites, respectively. Further, Dudek et al [34] found the hardness result to be 80 HBN for Mg recycled waste composites, and similar results have been reported by other researchers [35][36][37][38]. It is evident that the hardness results in the present study reflect the previously reported results.…”
Section: Hardness and Elongationsupporting
confidence: 91%
“…Cylindrical threaded Medium-carbon steel [97] AA6061-T6 and Ti6Al4V Cylindrical and tapered WC with 10% Co [98] Pure titanium (CP-Ti) and Ti6Al4V sheets Truncated conical [47] Al 6061-T6 to AISi 316 stainless steel Cylindrical WC-Co [99] AA1050 and AZ91 Cylindrical H13 steel [100] AA6061-T6 and pure Cu Cylindrical --- [101] Pure Al-pure Cu Cylindrical, tapered, straight triangle, and straight square W302 steel [102] Galvanized steel (GS) and mild steel Q235 Conical tapered WC [103] AZ31-AM60 --Tool steel [104] Table 3. FSW machines and characteristics [105].…”
Section: Al-cu Conicalmentioning
confidence: 99%